Utility of FilmArrayⓇ ME panel for prompt Neisseria meningitidis detection in non-cerebrospinal fluid samples– A case report. Issue 1 (January 2020) - García-Clemente, Paloma; Menéndez-Suso, Juan José; Falces-Romero, Iker; Escosa-García, Luis; Schüffelmann, Cristina; Cendejas-Bueno, Emilio
Abstract: The FilmArray Ⓡ Meningitis/Encephalitis Panel detects the 14 most frequent pathogens causing meningitis and/or encephalitis. The use of FilmArray ME with non-validated samples is seldom published in the literature. We describe the case of a 3-year-old child, diagnosed with acute meningoencephalitis, in whom the FilmArray Ⓡ ME technique successfully identified Neisseria meningitidis in both skin biopsy and whole blood samples.